Energy and the Macrodynamics of Agrarian Societies - Georgios Karakatsanis; Nikos Mamassis (Land, 2023)
For the present work, we utilized Leslie White’s anthropological theory of cultural evolutionism as a theoretical benchmark for econometrically assessing the macrodynamics of energy use in agrarian societies that constituted the human civilization’s second energy paradigm between 12,000 BC and 1800 AC. As White’s theory views a society’s ability to harness and control energy from its environment as the primary function of culture, we may classify the evolution of human civilizations in three phases according to their energy paradigm, defined as the dominant pattern of energy harvesting from nature. In this context, we may distinguish three energy paradigms so far: hunting–gathering, agriculture, and fossil fuels. Agriculture, as humanity’s energy paradigm for ~14,000 years, essentially comprises a secondary form of solar energy that is biochemically transformed by photosynthetic life (plants and land). Based on this property, we model agrarian societies with similar principles to natural ecosystems. Just like natural ecosystems, agrarian societies receive abundant solar energy input but also have limited land ability to transform and store them biochemically. As in natural ecosystems, this constraint is depicted by the carrying capacity emerging biophysically from the limiting factor. Hence, the historical dynamics of agrarian societies are essentially reduced to their struggle to maximize energy use by maximizing the area and productivity of fertile land –in the role of a solar energy transformation hub– mitigating their limiting factor. Such an evolutionary forcing introduced technical upgrades, like the leverage of domesticated livestock power as a multiplier of the caloric value harvested by arable and grazing land combined. According to the above, we tested the econometric performance of four selected dynamic maps used extensively in ecology to reproduce humanity’s energy harvesting macrodynamics between 10,000 BC and 1800 AC: (a) the logistic map, (b) the logistic growth map, (c) a lower limiting case of the Hassel map that yields the Ricker map, and (d) a higher limiting case of the Hassel map that yields the Beverton–Holt map. Following our results, we discuss thoroughly our framework’s major elaborations on social hierarchy and competition as mechanisms for allocating available energy in society, as well as the related future research and econometric modeling challenges.